Empowerment of Village Communities through the Creative Economy - Punur Ratsmi Janet (Akademi Sertifikasi Profesi Internasional, 2025)
This service seeks to bridge the disparity between the potential of local resources and the limited capacity of the residents of Village X in transforming items into competitive creative economy commodities, resulting in stagnant income. The primary issue encountered is the deficiency in knowledge and expertise about product innovation, business management, and the utilization of digital channels for marketing. This service activity aims to enhance the capabilities of village communities by providing intense training and ongoing support in the creative economy sector, particularly in handicrafts and culinary arts, while also expanding market access through digitization. This service's innovation is rooted in the implementation of the Community-Based Creative Incubation Model , which combines hard skills (production) with soft skills (management and digital marketing) training in a comprehensive group format. The service results indicated a substantial enhancement in product diversification, superior package quality, and a market reach expansion of up to 60% via e-commerce, which connected positively with a rise in the income of supported company groups